Mammary duct ectasia with bloody nipple discharge in a 5-month-old infant: A case report - El Yamani Fouda; Khaled Al Shamrani; Ahmad Al Hamdi; Mohammed Al Jurebi; Hesham Dahlan; Saud Erwi; Firas Al Ahmari; Nauman Rana (Elsevier, 2017)
Mammary ductal ectasia (MDE) with bloody nipple discharge (BND) appears to be exceptionally rare and presents a challenge for management to the consulting physician. We report A 5-month-old boy presented with a 3 weeks history of unilateral breast enlargement associated with intermittent spontaneous bloody nipple discharge. Ultrasound evaluation showed a 1.0 cm × 0.57 cm cystic mass in the right subareolar region with dilated ducts. Cytological evaluation of nipple discharge showed no malignant cells. The breast swelling and nipple discharge resolved spontaneously after 1 months without recurrence during the following 7 months. We conclude that mammary ductal ectasia is a benign and self-limited disorder in infancy and can be manged conservatively without any specific treatment to avoid unnecessary invasive surgical intervention.